Ultra processed food consumption and childhood obesity in food-insecure settings: A systematic review - Windi Indah Fajar Ningsih; Wilma Hannie Daniel; Rhipiduri Rivanica; Roza Holilah; Fatmalina Febry; Rizma Adlia Syakurah (Lentera Perawat, 2026)
Background: Childhood obesity continues to rise globally among populations  with food insecurity. Children’s reliance on ultra-processed foods (UPFs) is driven by their high energy density, affordability, and widespread accessibility. This condition contributes to the emerging paradox of the coexistence of food insecurity and childhood obesity associated with UPF consumption. Objective: This systematic review aims to systematically evaluate the association between ultra-processed food (UPF) consumption and the risk of obesity among children living in food-insecure settings. Methods: A systematic literature review was conducted using four electronic databases: ScienceDirect, PubMed, Cochrane Library, and Europe PMC, covering publications from 2016 to 2026. It was conducted from 7th April to 10th April. A total of 109 articles were identified through the initial search process, and 10 studies that met the predefined PICO framework and inclusion criteria were included in the final synthesis. Risk of bias was assessed using appraisal tools appropriate to each study design. Results: The included studies demonstrated that high consumption of ultra-processed foods (UPFs) was associated with an increased risk of overweight and obesity, poorer diet quality, and unhealthy feeding practices among children. Food insecurity was also linked to a greater likelihood of UPF consumption, lower dietary diversity, and reduced intake of fruits and vegetables. Conclusion: UPF consumption contributes to the increasing prevalence of childhood obesity in food-insecure settings. Food insecurity promotes poor-quality dietary choices and dependence on inexpensive processed foods, highlighting the need for policies aimed at improving access to healthy foods and enhancing education regarding UPF consumption among vulnerable populations.